Robotics: Science and Systems VIII 2012
DOI: 10.15607/rss.2012.viii.060
|View full text |Cite
|
Sign up to set email alerts
|

Rigidity Maintenance Control for Multi-Robot Systems

Abstract: Abstract-Rigidity of formations in multi-robot systems is important for formation control, localization, and sensor fusion. This work proposes a rigidity maintenance gradient controller for a multi-agent robot team. To develop such a controller, we first provide an alternative characterization of the rigidity matrix and use that to introduce the novel concept of the rigidity eigenvalue. We provide a necessary and sufficient condition relating the positivity of the rigidity eigenvalue to the rigidity of the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 34 publications
(47 reference statements)
0
55
0
Order By: Relevance
“…In our previous work (Zelazo et al, 2012), we introduced a related matrix termed the symmetric rigidity matrix. A main result of (Zelazo et al, 2012) was to provide a necessary and sufficient conditions for rigidity in the plane in terms of the positivity of a particular eigenvalue of the symmetric rigidity matrix; this eigenvalue we term the rigidity eigenvalue. This result is in the same spirit as the celebrated Fiedler eigenvalue 1 and its relation to the connectivity of a graph (Godsil and Royle, 2001).…”
Section: A Main Contributionsmentioning
confidence: 99%
“…In our previous work (Zelazo et al, 2012), we introduced a related matrix termed the symmetric rigidity matrix. A main result of (Zelazo et al, 2012) was to provide a necessary and sufficient conditions for rigidity in the plane in terms of the positivity of a particular eigenvalue of the symmetric rigidity matrix; this eigenvalue we term the rigidity eigenvalue. This result is in the same spirit as the celebrated Fiedler eigenvalue 1 and its relation to the connectivity of a graph (Godsil and Royle, 2001).…”
Section: A Main Contributionsmentioning
confidence: 99%
“…In determining and controlling the rigidity of the framework F x over time, one could continuously check infinitesimal rigidity and take suitable action towards preservation, as is explored in [19]. However, in [20] it is shown that almost all realizations of G are either infinitesimally rigid or flexible, indicating that rigidity can be approached generically, by examining the underlying graph G. Such a combinatorial characterization of graph rigidity in the plane was first described by Laman in [23], and is summarized as follows 1 : Theorem 2.1 (Graph rigidity, [23]): A graph G = (V, E) over realizations in R 2 having n ≥ 2 nodes is rigid if and only if there exists a subsetĒ ⊆ E consisting of |Ē| = 2n − 3 edges satisfying the property that for any non-empty subsetÊ ⊆Ē, we have |Ê| ≤ 2k − 3, where k is the number of nodes in V that are endpoints of (i, j) ∈Ê.…”
Section: A Rigidity Theorymentioning
confidence: 99%
“…Notice that Laman's theorem places restrictions on the network edges, thus we must only evaluate the Laman conditions during transitions in G. When compared to continuum methods such as [19], exploiting Theorem 2.1 in rigidity control yields a fundamentally more efficient and robust solution, as continuous computation and communication resources are not required for implementation. Such insights motivate the problem investigated in this work:…”
Section: A Rigidity Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Rigidity is a well-known and fundamental tool in the context of formation control based on distances [5], [6], [7]. Parallel rigidity [8], [9], that is, the bearing counterpart of 'distance rigidity', has also been recently introduced for controlling bearing-constrained formations.…”
Section: Introductionmentioning
confidence: 99%